The Conflict of Iran and the USA Post Arab Spring in the Middle East - Herison, Herison (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
This research discusses the conflict of Iran and the USA Post Arab Spring in the Middle East. Prior to the Iranian Islamic Revolution in 1979, the relationship between the two countries was amicable but deteriorated afterward. The involvement of the United States and Iran in proxy wars in Syria and Yemen reflects the tension in their relationship. The concept of Proxy War illustrates how conflict actors use third parties as arenas for power competition. This research employs a qualitative method with a descriptive analytical approach, uncovering relevant data and facts for analysis. The research concludes that the conflict is triggered by the United States' interests in the Middle East disrupted by Iran, leading to conflicts in military doctrine, geographical, socio-political order, and diplomatic fields. The United States adopts an offensive stance, while Iran adopts a defensive one.